FORMATION OF PERSONALITY QUALITIES OF A FUTURE MUSIC TEACHER IN PREPARATION FOR MUSIC INFORMATION SELECTION ACTIVITIES (Pedagogy of Higher and Secondary Education, 2009)
This article discusses some aspects of the preparation of future teachers of music to work on the selection of musical information, by creating a set of his personal qualities.
Keywords: selection; music information; personal qualities; training of teachers